2011
DOI: 10.1093/humrep/der314
|View full text |Cite
|
Sign up to set email alerts
|

A predictive score for testicular sperm extraction quality and surgical ICSI outcome in non-obstructive azoospermia: a retrospective study

Abstract: Thanks to better knowledge of TESE quality, the present score could help to improve care and pre-ICSI counseling for patients with NOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 38 publications
1
66
0
1
Order By: Relevance
“…Since thresholds for inhibin B and FSH together were associated with a greater OR than the threshold for the individual hormones alone, the measurement of inhibin B might substantially increase the predictive power of FSH. In fact, the combined use of FSH and inhibin B has proved to be of particular value in azoospermic conditions (13,35).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Since thresholds for inhibin B and FSH together were associated with a greater OR than the threshold for the individual hormones alone, the measurement of inhibin B might substantially increase the predictive power of FSH. In fact, the combined use of FSH and inhibin B has proved to be of particular value in azoospermic conditions (13,35).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…More recently, a couple of studies modeled a combination of some preoperative clinical parameters in the effort of achieving an higher diagnostic accuracy: Boitrelle et al [5] calculated a score from the combination of serum FSH and inhibin B levels plus testicular volume in patients undergoing conventional testicular sperm extraction (cTESE) obtaining an area under curve (AUC) value of 0.66, while Ramasamy and coworkers used an artificial neural network and were able to identify patients with or without testicular spermatozoa retrieved by microdissection testicular sperm extraction (microTESE) with a 60.8 % diagnostic accuracy [6]. Both models did not take into account testicular histology as potential predictive factor for sperm retrieval success, as they considered only pre-clinical, non invasive parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These men may be those with anticipated poor prognosis such that our study has included those with 'better' prognosis and therefore a higher sperm retrieval rate. In addition, while some authors suggest that hormonal profile or testicular volume may have provided prognostic information, 35,36 our information on hormonal profile of men was incomplete. Prior to TESE, FSH might have been checked up to 2 years because of the long waiting list for IVF, and therefore was not analysed in this study.…”
Section: Discussionmentioning
confidence: 93%
“…33 Seminal anti-Müllerian hormone and inhibin B are secreted by the Sertoli cells into the seminiferous tubules and therefore in theory are more direct markers of spermatogenesis, but their predictive value for successful TESE was not confirmed in a prospective study of 139 men with NOA by Mitchell et al 34 A combination of factors have been shown to fare better, and authors have described the use of a predictive score involving the total testicular volume, FSH, and inhibin B to predict the sperm retrieval rate in NOA. 35 There are several limitations to our study. The number of men who declined genetic testing or TESE was not known.…”
Section: Discussionmentioning
confidence: 94%